The Inhibitory Action of Capparisspinosa Leaves Against the Tumor and Leishmania - Al-Janabi, Nidal M S; Al-Halbosiy, Mohammad M F; Al-Badri, Samah R H (Al-Nahrain Journal of Science, 2019)
The leaves of the Capparisspinosa were collected from the eastern Radwaniya/Baghdad duringthe months April, May, June, July, September, and September. The leaves were extracted by water and alcohol.The effectiveness of anti-tumor and anti-leishmania for the water and alcohol extracts of al-Qabar leaf samples for May and September, which were characterized by the highest percentage of active compounds for the rest of the tested months, was evaluated by adopting the results of a previous study for the same researchers or chemical composition and leaf content of active compounds The concentrations of 250, 500, 1000 mg.L-1 were evaluated for anti-tumor efficacy. The anti-leishmania efficacy was tested at 250, 500 and 1000 mg L-1. The sample of the alcohol extract for May collected complex showed the highest anti-tumor activity at 63.5% at 500 mg.L-1and the highest efficacy of the samples of alcohol extract for September was 56.1% at the concentration of 250 mg.L-1, while the water extract for the May sample did not show any effectiveness even at the highest concentration 1000 mg L-1, but the September collected sample was effective at 49.3% In the case of the inhibitory efficacy of leishmania, the alcohol extract of the May sample did not show on inhibitory activity at the lowest concentration. The effectiveness of 41.3% was observed at 500 mg.L-1, but decreased to 14.8% at the highest concentration of 1000 mg L-1. Of the same month at the lowest concentration of 37.8% and decreased effectiveness there was an increase in the anti-leishmania effect of the September extract of the sample with increased concentration. There was of its effectiveness at the lowest concentration of a user and then reached 8 and 37% at the concentration of 500 and 1000 mg.L-1 with the same percentage, and the water extract for the September sample did not show any efficacy at the minimum and highest concentrations, except the concentration of 500 mg.L-1, which reached 11%.